2009
DOI: 10.1177/1545968309343216
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Functional Strength Training on Restoration of Lower-Limb Motor Function Early After Stroke: Phase I Randomized Controlled Trial

Abstract: included walking speed, knee extensor torque, and functional mobility (Rivermead). At outcome, both extraintensity groups showed greater increases in walking speed than the CPT group, but this reached significance only for the CPT + CPT group (P = .031). The CPT + CPT group also had a greater number of participants who walked at 0.8 m/s or above. No significant differences were observed for torque about the knee or for the Rivermead score. At follow-up, no significant differences were observed. These phase I r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 21 publications
(26 reference statements)
1
90
2
2
Order By: Relevance
“…9 Of the 80 trials included in this review, only 3 [16][17][18] reported a therapy dosage >22 hours. Therefore, the additional therapy time provided to participants in the circuit class therapy arm of our trial exceeds the therapy contrast reported in the majority of previous therapy dosage studies.…”
Section: Discussionmentioning
confidence: 99%
“…9 Of the 80 trials included in this review, only 3 [16][17][18] reported a therapy dosage >22 hours. Therefore, the additional therapy time provided to participants in the circuit class therapy arm of our trial exceeds the therapy contrast reported in the majority of previous therapy dosage studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 -22,25,27,29 Besides, because a standardized and universally accepted definition of "intensity" (or dose) is lacking, 2 operationalization in terms of workload input and output is difficult. 32,33 The intended and actually applied therapy time was reported in 4 publications and illustrates that the actual contrast in training time is approximately 75% of the preplanned contrast, 20,22,23,25 which may be explained by factors such as fatigue in the early phase poststroke, patients' schedules, or lack of staffing. Recording the actual therapy time was not common, and 7 of 14 studies did not provide any data about the applied therapy time.…”
Section: Downloaded Frommentioning
confidence: 99%
“…17-20,23-26,28 -30 In these studies, the additional therapy consisted of, for example, overground walking, 28 backward walking, 30 standing practice, 17,23 treadmill training, 24 or functional strength training. 20 The intervention period ranged from 2 21,26 to 20 weeks 25 with a frequency of 3 18,19,23,24,30 to 5 sessions 17,21,22,25,28,29 per week. The total intended additional therapy time ranged from 270 30 to 3000 minutes (Supplemental Table I).…”
Section: Study Identificationmentioning
confidence: 99%
“…Merely two of the thirteen participants in this study increased less than the minimally detectable change in walking speed. Other, frequently used, physiotherapy interventions for improving balance or gait, such as circuit training, functional strength training and body weight supported treadmill training, showed comparable increases for gait speed in patients within three months after stroke [50][51][52]. It is important to notice that the VR training intervention, just like the interventions described above, was part of the regular rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%